Applying Resource-Based View for Competitive Advantage in the it Industry: A Case Study on PT Metro Indonesian Software - Fabel Fachrezzy; Donard Games; Hafiz Rahman (Dinasti Review, 2025)
This study examines how PT Metro Indonesian Software leverages its firm resources to build a competitive advantage in the IT industry. Using the Resource-Based View (RBV) framework and the VRIO model, the research identifies the role of physical capital, human capital, and organizational capital in shaping the company's competitive positioning. Data was collected through semi-structured interviews with key informants, including company directors and employees, as well as non-participatory observations. The study highlights that the company effectively utilizes its technological infrastructure, skilled human resources, and agile development methodologies to maintain efficiency and innovation. However, challenges such as maintaining employee discipline, adapting to fast-changing industry trends, and cybersecurity threats remain critical considerations. The findings suggest that a continuous evaluation and strategic resource allocation are essential for sustaining long-term competitive advantage in the dynamic IT sector.